Ekotopska analiza Boča - Vovk, Ana (Geografski obzornik, 1994)
The successul protection of nature and qualitive evaluation of areas for different land use demand appropriate knowledge of all natural and social factors within of environment. All components of the landscape appear in various combinations. Their influence on land use and settling is of special importance. By quantitative evaluation of lithologhical structure, relief, hydrologhical, vegetational and soil characteristics, the smallest homogeneousunits - ecotops, can be determinated. The article represents a case study of ecotopic analysis on the example of the Boč mountain landscape.
Keywords: Boč; ekotopi; geografija; pokrajinska ekologija; raba tal